POTENSI DESA WISATA BONJERUK SEBAGAI DESTINASI WELLNESS TOURISM - Ulya, Baiq Nikmatul; Minanda, Hasnia; Budiatiningsih, Mahmudah; Kurniansah, Rizal (Warta Pariwisata, 2024)
The general objective of this research was to analyze the potential of Bonjeruk Tourism Village as a wellness tourism destination based on tourism destination components and wellness tourism criteria. This study is a qualitative descriptive research. Data collection was done through literature review, observation and interviews. The results showed that Bonjeruk Tourism Village has tourism destination components in the form of attractions, amenities, accessibility, and ancillary services that are complete and in good condition. Bonjeruk Tourism Village also fulfills the criteria of wellness tourism, where tourists visiting Bonjeruk Tourism Village gain physical, mental, environmental and spiritual experiences. However, Bonjeruk's tourism potential is still in need of more focused development.